Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Find the equation of the line that passes through (-1,2) and is perpendicular to 2 y = 2 x − 1 . Leave your answer in the form y = m x + c

Sagot :

The equation in slope-intercept form of the line that passes through the point (-1, 2) and is perpendicular to the line equation, [tex]2 y = 2 x - 1[/tex] is: [tex]y = -x + 1[/tex]

Recall:

Equation of a line in slope-intercept form is: [tex]y = mx + c[/tex], where, slope = m, and y-intercept = c.

Point-slope form is: [tex]y - b = m(x - a)[/tex]

The slope value of a line will be the negative reciprocal of the slope of the line it is perpendicular to. i.e. if the slope of a line is a, the slope of the line that it is perpendicular to will be -a.

Given:

  • The line passes through point (-1, 2)

  • Equation of line it is perpendicular to is: [tex]2 y = 2 x - 1[/tex]

To write the equation of the line that passes through (-1, 2), we need to find the slope value.

  • First, rewrite  [tex]2 y = 2 x - 1[/tex] and find its slope.

[tex]\frac{2y}{2} = \frac{2x}{2} - \frac{1}{2} \\\\y = x - \frac{1}{2}[/tex]

  • The slope (m) of [tex]2 y = 2 x - 1[/tex] is therefore 1.

  • Thus, the slope (m) of the line that passes through (-1, 2) will be the negative reciprocal of 1 = -1.

  • Write the equation of the line by substituting (a, b) = (-1, 2) and m = -1 into  [tex]y - b = m(x - a)[/tex]:

  • Thus:

[tex]y - 2= -1(x - (-1))\\\\y - 2 = -1(x + 1)[/tex]

  • Rewrite this in the form of [tex]y = m x + c[/tex]

  • Thus:

[tex]y - 2 = -x - 1\\\\y = -x - 1 + 2\\\\y = -x + 1[/tex]

Therefore, the equation in slope-intercept form of the line that passes through the point (-1, 2) and is perpendicular to the line equation, [tex]2 y = 2 x - 1[/tex] is [tex]y = -x + 1[/tex]

Learn more here:

https://brainly.com/question/12313302